Pola Interaksi Pendidik Dan Peserta Didik Dalam Pembelajaran Menulis Teks Deskripsi Kelas VII SMPN 31 Semarang - Marius Warkuta; Siti Ulfiyani; Eva Ardiana Indrariani (CV. Alim's Publishing, 2024)
Humans are individual creatures and social creatures. Thus, human life activities will always be accompanied by a process of interaction or communication, whether interaction with the natural environment, interaction with fellow individuals, or interaction between teachers and students, whether intentional or unintentional (Sardiman, 2004). The method used in this research is a descriptive method with a qualitative approach. This method is used because this research aims to describe interaction patterns in learning as they are. The researcher is the key instrument for combined data collection techniques, data analysis is qualitative, and the results of qualitative research emphasize meaning rather than general conclusions from an event. The data results are in accordance with the research objectives, namely in the form of one-way interaction patterns, two-way interaction patterns, and multi-way interaction patterns used in learning to write poetry. The results obtained from each of these data are (1) one-way interaction patterns (5 data), (2) two-way interaction patterns (6 data), and (3) multi-way interaction patterns (3 data). Based on these findings, it can be concluded that one-way interaction patterns and two-way interaction patterns are the interaction patterns most widely used between teachers and class VIII students in learning to write descriptive text.